Reaction time analysis in visual response using electromyography and electroencephalography - Yotani, K.; Tamaki, H.; Nakamoto, H.; Shibano, K.; Yuki, A.; Kirimoto, H.; Kitada, K.; Ogita, F.; Mori, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Visuo-motor related time (VMRT) can be calculated by subtracting the latency of motor-evoked potentials (MEPs) from premotor time (PMT) measured by electromyography (EMG) for simple reaction tasks (Yotani et al., 2011) and reflects the time elapsed from visual stimulation to the motor cortex through the visual cortex. Moreover, the peak latency in event-related potentials (ERPs) reflects the speed of information processing in the brain and can be recorded using electroencephalography (EEG). We assessed the relationship between VMRT and the latency of ERP components (P300 [P3] and visual evoked potentials [VEP]) to visual stimulation. Method: Seven healthy male subjects (mean age, 24±3 yrs) were asked to flex the right thumb as quickly as possible in response to a visual signal. EEG was recorded on the scalp at Fz, Cz, Pz and Oz during the task, and EMG was recorded from the right flexor pollicis braevis muscle simultaneously with production of the light signal. MEP latency was measured from the flexor pollicis braevis muscle using transcranial magnetic stimulation (TMS). P3 latency was measured at Fz, Cz and Pz. Three VEP component latencies (P1, N1 and P2) were measured at Oz. In addition, VMRT was calculated as PMT minus MEP latency. Results: Significant positive correlations were observed between Fz-, Pz- P3 latency and VMRT (r= 0.77-0.85, P<0.05), and no significant correlations were observed with the Cz-P3 latency. In the VEP, significant negative correlations were observed only between the Oz-P2 latency and VMRT (r=-0.76, P<0.05). Discussion/Conclusion: The ERP latencies of Fz-P3, Pz-P3 and Oz-P2 reflect the higher order brain processes. (Numata et al., 1998; Mehta et al., 2000). The results of the present study suggest that the VMRT is affected by those processing speed.